Caracterização e avaliação dos potenciais biotecnológico e funcional de microrganismos endofíticos de Vochysia divergens POHL do Pantanal mato-grossense - Lima, William Cardoso (2012)
The presence of endophytes living mutualisticamente with plant species that may contribute to certain plants can withstand different types of abiotic and biotic stresses. This work is the first report of V. divergens endophytic community. The isolation was performed in two different fungi resulting in 150, 64 in the dry season and 86 in the Pantanal wetland flooded period. The frequency of endophytic colonization was higher in the wet season. Chaetomium globosum and Penicillium sp1 were dominant during dry and Eupenillium sp. in the wet season. Trichoderma sp and Penicillium sp 1 were isolated in both periods. It was first observed mycorrhizae fungi endomicorrícos type in Paris and dark septate root cambará. The ecological role of these micro-organisms may eventually help in understanding the adaptation of this species in the Pantanal. A total of 61 endophytic fungi isolated from root V. divergens Pohl were evaluated for their ability to inhibit the growth of bacteria Enterococcus faecalis (ATCC 29212), Staphylococcus aureus (ATCC 25923), Staphylococcus saprophyticus (ATCC 43867) and Escherichia coli ( ATCC 25922). Of the tested strains, 12 four inhibited pathogenic bacteria tested. The genus Trichoderma - 43WE lineage and morphotype ms10w - 44W lineage and ms13w - 53W lineage strain were selected for analysis of the chemical profile. The hexane extract of the genus Trichoderma strain 43WE stood out for having the presence of caryophyllene, germacrene B and germacrene D in its fermented. This chemical profile motivated us to study the ethyl acetate extract of isolated, being found 4 - hidroxybenzenoetanol (tyrosol), benzeneacetic acid, propanal, 2,5 - dimethyl - hexan- 3 - one and 2 - propildecan - 1 - ol. In the hexane extract was possible to find a single major constituent ester bis (2-ethyl-hexyl) hexanedioic acid. The results of this bioassay indicate that endophytic fungi have the ability to inhibit the growth of human pathogens. Endophytic bacteria isolated from roots of V. divergens dry and flooded wetland, were characterized for their ability to produce the phytohormone indole acetic acid (IAA) and by their ability to solubilize phosphate. Characterized isolates of only five of the dry period had both the two characteristics analyzed in this work. Bacteria dry period showed a greater ability to solubilize phosphate that flooded and the production of IAA was only observed in isolated dry period.